Exploring gender equity in higher education pedagogy: A co-constructed comparative case study of Kazakhstan and India - Samuel, Nupur; CohenMiller, Anna; Anand, Abhinav; Rakisheva, Aigul; Saniyazova, Aray (Nordic Journal of Comparative and International Education (NJCIE), 2025)
Higher education spaces are embedded within the larger ecosystem of societies, and they simultaneously endorse, question, critique, and transform societal norms. Exploring gender equity in higher education curriculum and pedagogy involves examining the systemic, social, and cultural dynamics that influence gender disparities within academic spaces and society. Examining gender mainstreaming in higher education pedagogy is essential to address systemic biases, promote inclusive teaching practices, and ensure that all students, regardless of gender, have equal opportunities to succeed. A co-constructed comparative case study of Kazakhstan and India provides a unique lens to understand these disparities and devise strategies to address them. In this study, we analyzed data collected from two universities to understand the challenges and curriculum and pedagogic practices that can create more equitable spaces. By adopting a collaborative research approach, this comparative study reveals common challenges, successful strategies, and practices that can help create gender equity and inclusivity in higher education. Findings indicate that while gender awareness and sensitivity are in the minds of the stakeholders, they are not embedded in the curriculum. Data analysis further demonstrates the need to incorporate more representative voices from different genders across the curriculum, both as textual material and as more diverse faculty. We argue that deep-rooted patriarchal norms and systemic barriers that continue to hinder gender inclusivity can be addressed not by creating specific courses or programs but by a holistic, inclusive curriculum that embeds gender equity in every aspect of higher education.